The effect of land use on benthic communities in Hawkes Bay streams of differing geology : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Ecology at Massey University - Gibson, Jason Ross (Massey University, 1999)
Benthic macroinvertebrate and periphyton communities of streams draining four different land use types within four distinct geological types were sampled between December 1996 and January 1997. Catchment land use comprised either standing mature or logged exotic forest, native forest, or hill country pasture. The geological types of these catchments were either Mesozoic sandstone-greywacke, Pleistocene-greywacke, Tertiary mudstone, or limestone in origin. Pastoral stream invertebrate community structure was significantly different from that found in forested streams, with no clear distinction separating communities from standing exotic, logged exotic, and native forest sites. Pastoral communities were dominated by dipterans and trichopterans. while in contrast, macroinvertebrate communities in streams draining sandstone-greywacke catchments were dominated by ephemeropterans and plecopterans, showing a clear influence of catchment geology on benthic macroinvertebrate communities. This sandstone-greywacke effect appeared to be independent of land use. Periphyton biomass was greatest in pastoral and exotic sites, particularly those draining limestone catchments. High nutrient and conductivity levels, both of which are characteristic of limestone streams, appeared to override the effect of light restrictions on periphyton growth in exotic forest sites. Overall, both geology and land use played major roles in determining the structure of stream benthic communities, with factors such as altitude and stream temperature also important influences on these communities. In November and December 1997, nutrient, shade, and disturbance effects were examined in periphyton communities colonising artificial substrates. These substrates were left in the 8 forested Hawkes Bay streams for 28 days with disturbance treatment substrates being physically abraded every 7 days. Nutrients (N + P) were added to nutrient treatment substrates and polythene cloth was used to create an artificially shaded environment for shade treatment substrates. Light availability and percentage canopy cover had the greatest effect upon periphyton, with light limitation being exhibited in closed canopy systems. Nutrient supply was also a factor determining periphyton biomass at both open and closed sites, although only up to a limit. Physical disturbance successfully removed organic matter from substrates as well as reducing chlorophyll a levels at open sites, however light and nutrient levels were more important determinants of chlorophyll a concentrations. In summary, both land use and geology play a considerable role in influencing both macroinvertebrate community structure and periphyton biomass. The geological influence was mediated through direct effects on nutrient inputs into the stream (as measured by conductivity), as well as by the indirect influence upon stream water temperatures. The influence of land use on benthic communities is predominantly as a result of shade levels created by vegetation types and enrichment levels derived from agriculturally influenced land. These results are of particular importance when comparing or analysing results from studies involving different land use types, particularly when these land uses cover a range of altitudes or are found in more than one geological type.
Keywords: New Zealand; Hawke's Bay; Freshwater invertebrates; Environmental aspects; Stream ecology; Geology; Land use